Six Sigma as a competitive strategy: main applications, implementation areas and critical success factors (CSF) - López, Aida (2019)
In the search for competitiveness, organizations adopt strategies to increase the cost-effectiveness of their operations and improve its position in the market. Six Sigma (SS) that was initially developed as a methodology to eliminate defects in production systems has been transformed into an operational improvement strategy, in addition of extending the areas for its deployment. This article summarizes the results of a systematic review of SS literature related to the main fields and purposes of application. Additionally, an analysis ofthe most important Critical Success Factors (CSF) is presented, which are: Management Support and Commitment, Relationship with customers, Organizational Culture, Education and Training, Organizational Infrastructure and Communication. Finally, several research lines are proposed and areas of SS application of interest to the researchers and professionals of continuous improvement.